Sentidos e significações da gestão democrática: da previsibilidade à efetividade nas escolas públicas estaduais do município de Itapetininga/SP - Moraes, Telma Elizabete de (Universidade Federal de São Carlos, 2015)
The present work casts doubts on the perceptions of parents, students, regular teachers, coordinator teachers and principals from the state schools at the city of Itapetininga as much as the complete sense and meaning of democratic management in the dimension of predictability, effectiveness and implications that they result, through punctual fragments articulated in the literature area. the study was anchored in the premises of search qualitative and quantitative from interviews with the directors of the school and semi- structured questions were led to the participants and for its analysis we searched for four specific categories in which we could see clearly the results from the people who were the subject of study: 1) The signification of democracy, with theorical basis essentially from Bobbio (1998, 2000, 2013); 2) The signification of the representative organs (APM and Conselho de Escola and Grêmio estudantil) with basis on Gohn (2011), Hora (2012), Lima (2013) Riscal (2009) Luiz, Riscal and Ribeiro (2013), Oliveira and Silva (2005), Paro (2007) Ramos and Conti (2013); 3) The administration of democratic schooll studied from Hora (2012), Lima (2013), Lima, Aranda and Lima (2013), (Meirieu (2005), Oliveira (2013), Paro (1998, 1999, 2007, 2008 e 2010); 4) The resignification of the school quality, with theorical reference in Benevides (1996), Enguita (2001), Frigotto (2001), Gentili (2001), Lima (2014), Paro (1998, 1999, 2000, 2007, 2010, 2012, 2014) and Prado (2014). The contextualization of the do object of research also aroused the investigation of the course and patterns of the school administration in which took place on the republican time, such as the analysis of relation between schoool administration and enterprise administration. These investigations were developed on the theorical basis from Gallindo and Andreotti (2012), Ganzelli (2005), Clark, Nascimento and Silva (2012), Félix (1985), Lourenço Filho (1976), Minto (2012), Penteado and Bezerra (2012), Pereira (2006), Ribeiro (1995), Romanelli (2014), Sander (2005, 2007), Xavier (1992). Our main conclusions are the evidence that the conception of direct democracy imposed itself dominant among the people involved as been the ideal; there is a distance between the concept of democracy stood up by Bobbio (2000) and what the people involved in the study understand; it is not clear yet as for the main elements of representative democracy; there is the understanding about the attributions, the nature and the reasons of the school organs, however, in the representation, it ignores the question on the role of social control of education; there is a conformist trende in a non participation of parents at the make-decision rooms; everybody recognizes that the democratic administration contributes to the quality of education, although, it is necessary to think about which are the indicators of quality in the democratic education and, finally the conclusion is that between the predictability and the effectiveness of democratic administration, there is still a long way to be run.
Senses and meanings of democratic management: from the predictability to effectiveness in public schools in the city of Itapetininga
Keywords: Democracia; Gestão escolar; Participação; Qualidade de ensino; Escolas organização e administração; Escolas públicas Itapetininga (SP); Democracy; School manegement; Communion; Teaching quality; CIENCIAS HUMANAS::EDUCACAO